FLUORINATED POLYMER-FILMS FROM RF PLASMAS CONTAINING BENZENE AND SULFUR HEXAFLUORINE - Durrant, S. F.; Mota, Rogério Pinto [UNESP]; Demoraes, MAB (Elsevier B.V., 1992)
Mixtures of C6H6 and SF6 were polymerized in an r.f. discharge. Actinometry (quantitative optical emission spectroscopy) was used to determine trends in the plasma concentrations of the species F, H and CH as a function of the proportion of SF6 in the feed. Infrared spectroscopy and electron spectroscopy for chemical analysis were employed to characterize the deposited material. Increasing proportions of SF, in the feed produced increased fragmentation of the benzene molecules and greater fluorination of the deposited material. The deposition rate, as determined by optical interferometry, was found to be enhanced about 4 times by the presence of 10-20% SF6 in the feed. At 50% SF6 in the feed, deposition rates were greater than in pure C6H6 plasmas despite the (probably large) etching effect of atomic fluorine from the discharge. Relationships between the plasma composition, electron density and temperature, film composition and growth rate are discussed.